Motif Tabuh Kendang Banyuwangi Pada Iringan Tari Jejer Gandrung Gaya Cak Munarno - Aprian, Willy; Supriadi, Didin (Program Studi Pendidikan Musik, 2023)
This study aims to describe the Banyuwangi drum percussion motif found in the Jejer Gandrung Dance with the cak Munarno percussion style. The research method used is descriptive qualitative research, this research was carried out at the TMII Pavilion in East Java and at the home of the resource person which was held from February 26, 2022 to May 17, 2022. The data obtained were the result of carrying out observations, interviews, documentation, and journals collected. obtained. The result of this research is that Banyuwangi art has unique characteristics and is very thick, by obtaining descriptions of various kinds of Banyuwangi drum beat motifs that exist, especially drums to the accompaniment of the Jejer Gandrung dance. With this, traditional arts actors in DKI Jakarta and The Sanggars who are still active in performing and preserving the arts of the archipelago can understand the meaning and can give performances properly, both musicians and dancers. In the world of education, of course, this wasp motif can be used as teaching material for music educators, especially traditional music in providing Banyuwangi art material, because this Gandrung art is an art that is already familiar and has become an icon of Banyuwangi Art itself.